2012
DOI: 10.1148/radiol.12110460
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cholecystitis: Preoperative CT Can Help the Surgeon Consider Conversion from Laparoscopic to Open Cholecystectomy

Abstract: The absence of gallbladder wall enhancement (associated with the presence of gangrenous acute cholecystitis) and the presence of a gallstone in the gallbladder infundibulum are associated with conversion from laparoscopic to open cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 20 publications
2
34
0
4
Order By: Relevance
“…Pericholecystic fluid on ultrasound was a predictor in one study [48] , but not in 2 other studies [40,42] . However, when evaluated on CT, the same measures were not risk factors [31] .…”
Section: Medical Imagingmentioning
confidence: 92%
See 2 more Smart Citations
“…Pericholecystic fluid on ultrasound was a predictor in one study [48] , but not in 2 other studies [40,42] . However, when evaluated on CT, the same measures were not risk factors [31] .…”
Section: Medical Imagingmentioning
confidence: 92%
“…Meta-analysis on 3 of these studies [11,31,33] (n = 20,748, median NOS = 8 (range 7-9), I 2 = 74%) found a pooled OR of 1.85 (95% CI 0.92-3.75; fig. 2 c).…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, CT has been advocated as a useful modality in preoperative planning, with the absence of gallbladder wall enhancement and/or the presence of a stone within the infundibulum associated with conversion from laparoscopic to open cholecystectomy. Prior knowledge of these imaging findings may therefore help guide the appropriate surgical approach [20]. …”
Section: Summary Of Literature Reviewmentioning
confidence: 99%
“…Preoperative prediction of patients at risk of conversion can be very useful for surgical planning and outcomes (21). In the radiology literature, a recent study by Fuks et al reported imaging findings on CT that can predict conversion (22). With the additional functional information, GDE-MRC may be helpful in risk stratification of the patients and in preoperative planning.…”
Section: Discussionmentioning
confidence: 99%